2023
DOI: 10.3390/en16155710
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Model for Wake-Induced Aerodynamic Interaction of Wind Turbines

Esmail Mahmoodi,
Mohammad Khezri,
Arash Ebrahimi
et al.

Abstract: Wind turbine aerodynamic interactions within wind farms lead to significant energy losses. Optimizing the flow between turbines presents a promising solution to mitigate these losses. While analytical models offer a fundamental approach to understanding aerodynamic interactions, further development and refinement of these models are imperative. We propose a simplified analytical model that combines the Gaussian wake model and the cylindrical vortex induction model to evaluate the interaction between wake and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Its accuracy has also been proved [49]. Unlike the single theoretical derivation [29][30][31] or statistical research methods [42][43][44], this paper combines the velocity analysis based on the wake model with the power analysis based on SCADA data. It evaluates the wake energy efficiency loss of wind farms from both theoretical and practical perspectives, and the results are more scientific and accurate.…”
Section: Criteria For Evaluating Wake Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Its accuracy has also been proved [49]. Unlike the single theoretical derivation [29][30][31] or statistical research methods [42][43][44], this paper combines the velocity analysis based on the wake model with the power analysis based on SCADA data. It evaluates the wake energy efficiency loss of wind farms from both theoretical and practical perspectives, and the results are more scientific and accurate.…”
Section: Criteria For Evaluating Wake Lossmentioning
confidence: 99%
“…In addition, they investigated the effects of different incoming turbulent boundary layer flows on large wind farms and found that increasing the intensity of incoming turbulence is favorable to the recovery of wake velocity compared to changing the layout arrangement of wind turbines, which improves the overall power generation [27,28]. Mahmoodi E et al [29] combined the Gaussian wake model and the cylindrical vortex induction model to derive a new model to analyze the interaction of wake and induction zones. The velocity deficit characteristics were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…In the article [7], the aerodynamic wake of the side wind is studied with the help of vortex methods, taking into account the different movement for the near and far wake. And in [8], a simplified analytical model is proposed, which combines the Gaussian wake model and the model of the induced cylindrical vortex to evaluate the interaction between the wake zones. The paper [9] studies the characteristics of the speed of movement with consideration of turbulence and taking into account superposition for aligned wakes.…”
Section: Introductionmentioning
confidence: 99%